Proteomic, gene and metabolite characterization reveal the uptake and toxicity mechanisms of cadmium sulfide quantum dots in soybean plants. Issue 10 (17th September 2019) - Majumdar, Sanghamitra; Pagano, Luca; Wohlschlegel, James A.; Villani, Marco; Zappettini, Andrea; White, Jason C.; Keller, Arturo A.
Abstract : Cadmium sulfide quantum dots regulate nanomaterial-specific unique transmembrane transport system and metabolic processes in soybean plants. Abstract : Nanomaterial-specific response of quantum dots and the underlying mechanisms of their interaction with plants are poorly understood. In this study, we investigated the mechanism of cadmium sulfide-quantum dot (CdS-QD) uptake and stress response in soybean ( Glycine max ) plants using sensitive bio-analytical techniques. We adopted shotgun-proteomics and targeted analysis of metabolites and gene expression in the tissues of soybean plants exposed to 200 mg L −1 CdS-QDs in vermiculite for 14 days. The molecular response in the soybeans as a function of surface coatings on CdS-QDs, specifically, trioctylphosphine oxide, polyvinylpyrrolidone, mercaptoacetic acid and glycine was also tested. The biological response of CdS-QDs was compared to Cd-ions and bulk-CdS to identify the nanomaterial-specific response. The transmembrane proteins involved in uptake and genes including NRAMP6 and HMA8 were regulated differently in CdS-QD-treated plants compared to Cd-ion-treated plants. The ATP-dependent ion-transporters in the membranes presented feedback mechanisms in the soybean roots to restrict the uptake of CdS-QDs and simultaneously altered the mineral acquisition. CdS-QDs perturbed major metabolic pathways in soybeans including glutathione metabolism, tricarboxylic acid cycle, glycolysis, fatty acid oxidation and biosynthesis of phenylpropanoid and amino acids. This study provides clear evidence that the toxic responses and tolerance mechanisms in plants are specific to CdS-QD exposure and not entirely due to leaching of Cd ions.